2017
DOI: 10.1016/j.rboe.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Do patients lose weight after total knee replacement?

Abstract: ObjectiveSeveral studies show that patients undergoing total knee arthroplasty (TKA) tend to maintain or gain weight after the procedure, which would result in increased wear of the prosthesis and new surgical interventions in a smaller period of time in comparison with patients with adequate body mass index (BMI). The aim of this study was to investigate the effect of TKA surgery on these patients’ BMI.MethodsInitially the records were analyzed, chosen at random from 91 patients undergoing TKA during the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…18,24,25 Previous studies have shown that patients undergoing TKA do not experience a significant change in BMI. 26 -29 Our study also found no significant change in BMI before and after TKA. This finding, in addition with previous studies, suggests that the improvements in knee function and pain that can result from TKA may not translate to any significant weight loss in patients.…”
Section: Discussionsupporting
confidence: 46%
“…18,24,25 Previous studies have shown that patients undergoing TKA do not experience a significant change in BMI. 26 -29 Our study also found no significant change in BMI before and after TKA. This finding, in addition with previous studies, suggests that the improvements in knee function and pain that can result from TKA may not translate to any significant weight loss in patients.…”
Section: Discussionsupporting
confidence: 46%
“…The Framingham Study established a causal relationship between weight and knee OA,10 and that relationship poses a specific challenge for treatment. Total joint replacement, especially of the knee, is not expected to be as successful or complication free in patients who are more obese,34 and total joint recipients often do not lose weight or become more active after replacement, either 35–37. Our results add to the evidence, therefore, that both these epidemics—obesity and OA—are expected to continue and create challenges into the future.…”
Section: Discussionmentioning
confidence: 69%
“…This is potentially important in the light that patients who underwent TKA and lost weight thereafter were reported to have better clinical outcome scores than patients who gained weight in the postoperative period [48]. However, recent literature indicates the patient's bodyweight to be maintained after TKA [49][50][51], suggesting a minor possible impact of weight change on our results. The percentage of patients in obesity class II and III was relatively low, compared to reports in other countries with two-thirds of our patient cohort clustered in the overweight / pre-obese and class I obese categories.…”
Section: Discussionmentioning
confidence: 80%